The mesenchymal compartment in myelodysplastic syndrome: Its role in the pathogenesis of the disorder and its therapeutic targeting - Pontikoglou, Charalampos G.; Matheakakis, Angelos; Papadaki, Helen A. (Frontiers in Oncology, 2023)
Myelodysplastic syndromes include a broad spectrum of malignant myeloid disorders that are characterized by dysplastic ineffective hematopoiesis, reduced peripheral blood cells counts and a high risk of progression to acute myeloid leukemia. The disease arises primarily because of accumulating chromosomal, genetic and epigenetic changes as well as immune-mediated alterations of the hematopoietic stem cells (HSCs). However, mounting evidence suggests that aberrations within the bone marrow microenvironment critically contribute to MDS initiation and evolution by providing permissive cues that enable the abnormal HSCs to grow and eventually establish and propagate the disease. Mesenchymal stromal cells (MSCs) are crucial elements of the bone marrow microenvironment that play a key role in the regulation of HSCs by providing appropriate signals via soluble factors and cell contact interactions. Given their hematopoiesis supporting capacity, it has been reasonable to investigate MSCs' potential involvement in MDS. This review discusses this issue by summarizing existing findings obtained by in vitro studies and murine models of MDS. Furthermore, the theoretical background of targeting the BM-MSCs in MDS is outlined and available therapeutic modalities are described